Severe allergic rash induced by icodextrin: case report and literature review - Huang, Yiqi; Fu, Tianxiao; Zhang, Yanling; Shen, Weigang; Sang, Weiwei; Han, Meixiang; Wang, Fang; Chen, Fenjuan (Frontiers in Medicine, 2024)
Background: Icodextrin is a type of peritoneal dialysis (PD) osmolyte that can be extended retention times (8-16 hours) and may offer a viable alternative to conventional glucose dialysis solutions for PD patients. Nonetheless, prolonged use of icodextrin may lead to allergic rash, and rarely severe skin lesions.In February 2024, a 45-year-old male was admitted to the Department of Nephrology at Shaoxing Second Hospital presenting with a 3-day history of intense generalized pruritic erythematous rash. Physical examination revealed diffuse erythematous pruritic rash and exfoliative rash, particularly on the abdominal. Abnormal laboratory findings included elevated eosinophil count and total IgE levels, indicative of an allergic rash. Standard anti-allergic regim was initiated. However, On the third day in the hospital, the patient developed new pustules on his neck and arms. Subsequent historical investigation uncovered that the individual had previously administered icodextrin two weeks prior due to volume overload, and the last intraperitoneal administration time was second day of hospitalisation. The dermatologist rendered a diagnosis of generalized exfoliative rash and acute localized exanthematous pustulosis (ALEP) induced by icodextrin, and initiated prophylactic antimicrobial therapy accordingly. Furthermore, the patient declined to undergo a skin biopsy. Noteworthy is the observation that the rash ameliorated and the pustules resolved by the seventh day post-admission. Presently, the patient is still under clinical follow-up.This article aims to report the first case of severe allergic rash caused by icodextrin in Chinese PD patients and highlight the potential for icodextrin to trigger ALEP. A literature review of similar cases found that severe allergic rash induced by icodextrin is rare, the underlying mechanism remains poorly understood, and the prognosis is positive with proper treatment.